Pediatric idiopathic steroid-sensitive nephrotic syndrome: diagnosis and therapy —short version of the updated German best practice guideline (S2e) — AWMF register no. 166-001, 6/2020 - Ehren, Rasmus; Benz, Marcus R.; Brinkkötter, Paul T.; Dötsch, Jörg; Eberl, Wolfgang R.; Gellermann, Jutta; Hoyer, Peter F.; Jordans, Isabelle; Kamrath, Clemens; Kemper, Markus J.; Latta, Kay; Müller, Dominik; et al. (Pediatric nephrology (Berlin, West), 2021)
Idiopathic nephrotic syndrome is the most frequent glomerular disease in children in most parts of the world. Children with steroid-sensitive nephrotic syndrome (SSNS) generally have a good prognosis regarding the maintenance of normal kidney function even in the case of frequent relapses. The course of SSNS is often complicated by a high rate of relapses and the associated side effects of repeated glucocorticoid (steroid) therapy. The following recommendations for the treatment of SSNS are based on the comprehensive consideration of published evidence by a working group of the German Society for Pediatric Nephrology (GPN) based on the systematic Cochrane reviews on SSNS and the guidelines of the KDIGO working group (Kidney Disease - Improving Global Outcomes).